Monsoon effects on the geochemical of surface sediment in the nearshore area off Terengganu, Malaysia - Hasrizal Shaari (Institut Oceonography, 2011)
This thesis investigates the geochemical characteristics of the surface sediments of Terengganu nearshore area during the pre- and post-monsoon seasons and sedimentation rate. Sampling activities were carried out twice in two years, in September 2002 and April 2003. The samplings covered an area approximately 750 nautical square miles. Sampling points were setup in seven transects which consisted of seven points each. For this work, sediment grain size, organic carbon, heavy metal and also sedimentation rates.